Submandibular lipoma in elderly female in mid western Nepal: A Case Report - Tulachan, Bishow; Borgohain, Buddha Nath (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: The submandibular lipomas are relatively rare entity. The reported age of the patients were from birth to 84 years old, and average being 55.7 years. These are mainly asymptomatic and mostly cause aesthetic concerns. Deep lipomas, especially in the head and neck, are not commonly reported. To our knowledge there’s not even a single publication regarding the lipoma in the submandibular region in our mid western region as well as in our country. Presentation of case: A 72 years old female presented with complaints of painless progressive neck swelling in the right submandibular region for about 2 years. Clinically, it was thought to be submandibular gland neoplasm/ lymphadenopathy. Ultrasonography (USG) and fine-needle aspiration cytology (FNAC) were done. It was negative for malignancy. She underwent excision of the mass under general anesthesia without postoperative complications. The histopathology confirmed it to be lipoma. Discussion: Lipoma is a common benign mesenchymal tumour that is found almost anywhere in the body. However, a large lipoma is relatively rare in the submandibular region. On clinical doubt, one can rely on USG / MRI (magnetic resonance imaging) and FNAC to rule out diagnostic dilemma. The treatment of choice is simply excision. Conclusion: It’s a rare entity and may be the first report of a lipoma in the submandibular region in an elderly people. One should rule out its possibility while going through the submandibular region diseases. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 46-49